2020
DOI: 10.1002/app.50195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, strain rate, and cyclic loading on mechanical behavior of silane‐modified polyurethane sealant

Abstract: To evaluate the mechanical properties of modified polyurethane sealants in engineering applications, the influences of temperature, strain rate, and cyclic loading on the mechanical properties of silane‐modified polyurethane sealant were experimentally investigated. The monotonic tensile experiments with various strain rates and temperatures were conducted, and strain rate and temperature dependent nonlinear stress–strain curves were obtained. The results showed that the silane‐modified polyurethane sealant ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The physical properties of HP-172B after curing are presented in Table 1. 4 In the cruciform specimen design, it is considered that the stress concentration location of the specimen under biaxial loading condition should be in the center of the cruciform specimen. The four tensile arms of the specimen are designed to be circular arcs to reduce the stress concentration here.…”
Section: Materials and Specimen Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical properties of HP-172B after curing are presented in Table 1. 4 In the cruciform specimen design, it is considered that the stress concentration location of the specimen under biaxial loading condition should be in the center of the cruciform specimen. The four tensile arms of the specimen are designed to be circular arcs to reduce the stress concentration here.…”
Section: Materials and Specimen Preparationmentioning
confidence: 99%
“…The results revealed that the changes in ratcheting strain and ratcheting strain rate are proportional to the stress amplitude and the mean stress, and the loading history has a significant influence on the ratcheting strain. Zhang et al 3,4 performed experimental investigations on silane-modified polyurethane sealant and TB991 weld sealant under uniaxial cyclic loading, analyzing the effects of strain amplitude, mean strain, temperature, loading rate, and loading history on fatigue performance by investigating cyclic stress relaxation, slope variable, and dissipated energy. Tao et al [5][6][7] studied the influence of mean stress and shear stress amplitude on the fatigue life of epoxy resin through uniaxial tensile and torsional fatigue tests.…”
Section: Introductionmentioning
confidence: 99%
“…The modified PU does not release CO 2 gas when it cures with moisture from the air, overcoming the inherent deficiencies of PU such as inadequate weathering performance, resulting in an outstanding performance similar to that of silicone. [9][10][11][12][13][14] Polyurethane is characterized by exceptional strength, toughness, and elasticity over a broad range of hardness, which can be achieved by varying the ratio of hard and soft segments. The NCO:OH ratio can be adjusted to alter this ratio, resulting in changes in molecular weight, glass transition temperature, thermal stability, hardness, and tensile strength among other properties.…”
Section: Introductionmentioning
confidence: 99%
“…The modified PU does not release CO 2 gas when it cures with moisture from the air, overcoming the inherent deficiencies of PU such as inadequate weathering performance, resulting in an outstanding performance similar to that of silicone. [ 9–14 ]…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical property is one of the integral indicators for soft materials' application. Characteristic parameters such as Young's modulus, tensile strength and breaking elongation can be used to characterize the mechanical properties of soft materials [16][17][18][19]. Compared with metal materials and other polymer materials, large deformation under small load is a typical characteristic of soft materials.…”
Section: Introductionmentioning
confidence: 99%